Bound within boundaries: Do protected areas cover movement corridors of their most mobile, protected species?. Issue 6 (6th May 2021) - Hofmann, David D.; Behr, Dominik M.; McNutt, John W.; Ozgul, Arpat; Cozzi, Gabriele
Abstract: Conserving and managing large portions of land to connect wildlife reserves is an increasingly used strategy to maintain and restore connectivity among wildlife populations. Boundaries of such conservation areas are often determined based on expert opinion and socio‐political constraints, yet the extent to which they match species' movement corridors is rarely examined. This is mainly due to a lack of data, particularly on wide‐ranging movement behaviour such as dispersal. Nevertheless, empirically assessing the adequacy of protected areas is key for the implementation of targeted management actions and efficient use of limited conservation funds. Between 2011 and 2019, we collected high‐resolution GPS data on 16 dispersing African wild dog Lycaon pictus coalitions from a free‐ranging population in the Kavango–Zambezi Transfrontier Conservation Area (KAZA‐TFCA). Spanning five countries and 520, 000 km 2, the KAZA‐TFCA is the world's largest transboundary conservation area and a prime example for international conservation efforts. We used integrated step selection analysis to estimate habitat selection of dispersers and to create a permeability surface for the KAZA‐TFCA. We compared landscape permeability across different regions within the KAZA‐TFCA as well as outside its boundaries. Lastly, we calculated least‐cost paths and corridors to verify that major movement routes were adequately encompassed within the KAZA‐TFCA. Permeability within the boundaries of the KAZA‐TFCA was more than double compared to areas outside it. Furthermore, we observed a fivefold permeability difference among the five KAZA‐TFCA countries. We also showed that major movement corridors of wild dogs ran within the KAZA‐TFCA, although some minor routes remained formally unprotected. Differences in permeability were mainly related to different degrees of human activities across regions, and to the presence or absence of rivers, swamps and open water. The relationship between permeability and other landscape features was less pronounced. Synthesis and applications . In this study, we showed how pertinent dispersal data of a highly mobile species can be used to empirically evaluate the adequacy of already existing or planned protected areas. Furthermore, we observed regional differences in landscape permeability that highlight the need for a coordinated effort towards maintaining or restoring connectivity, especially where transboundary dispersal occurs. Abstract : In this study, we showed how pertinent dispersal data of a highly mobile species can be used to empirically evaluate the adequacy of already existing or planned protected areas. Furthermore, we observed regional differences in landscape permeability that highlight the need for a coordinated effort towards maintaining or restoring connectivity, especially where transboundary dispersal occurs.